'Through a Glass Darkly': Some Thoughts on the Portrait and the Problematics of Meaning - Graham Clarke (Vestiges: Traces of Record, 2018)
Editorial Note This essay was written in 2005 as part of the preparation for the exhibition in the National Portrait Gallery, London of the work of two Cameroonian photographers. It was not intended for the catalogue but for a follow-up collection which, in the end was never completed, and Graham Clarke subsequently died. It has been included here with the kind permission of his family to make the work available. Editorial input has been limited to the identification of the images concerned (not always straightforward) and the preparation of the bibliography. Readers should note that the captions were not available when Graham Clarke wrote this essay. He was responding to a set of images without context (later provided in Zeitlyn 2005 and other essays in Swenson (ed.) 2005, which have been added to the bibliography for convenience). DZ 1 March 2018 Abstract In this posthumously published essay Graham Clarke, the art historian and expert on photography, reflects on a series of Cameroonian photographs that were exhibited at the National Portrait Gallery in London in 2005